Recombinant Lactococcus lactis Expressing Grass Carp Reovirus VP6 Induces Mucosal Immunity Against Grass Carp Reovirus Infection - Wang, Nan; Li, Jiahao; Wang, Yajun; Wang, Yingying; Zhang, Defeng; Shi, Cunbin; Li, Yingying; Bergmann, Sven M.; Mo, Xubing; Yin, Jiyuan; Wang, Qing (Frontiers in Immunology, 2022)
Grass carp haemorrhagic disease caused by grass carp reovirus II is a serious disease of the aquaculture industry and vaccination is the only effective method of GCRV protection. In this study, Lactococcus lactis was used as oral vaccine delivery to express the GCRV II VP6 protein. We evaluated the protective efficacy of the live vaccine strain to induce mucosal immune protection. After oral administration, the recombinant strains remained in the hindgut for antigen presentation and increased the survival rate 46.7% and the relative percent survival 42.9%, respectively versus control vaccination. Though L. lactis alone can induce the inflammatory response by stimulating the mucosal immune system, the recombinant L. lactis expressing VP6 greatly enhanced nonspecific immune responses via expression of immune related genes of the fish. Furthermore, both systemic and mucosal immunity was elicited following oral immunization with the recombinant strain and this strain also elicited an inflammatory response and cellular immunity to enhance the protective effect. L. lactis can therefore be utilized as a mucosal immune vector to trigger high levels of immune protection in fish at both the systemic and mucosal levels. L. lactis is a promising candidate for oral vaccine delivery.